Constructing an Optimal Portfolio with a Single Index Model on the Shares of Bumn Companies Listed in the IDXBUMN20 Index on the Indonesia Stock Exchange - Bagus Wicaksono Kurniawan; C. Ambar Pujiharjanto; Nilmawati Nilmawati (West Science Business and Management, 2023)
This study aims to determine the optimal portfolio using a single index model on the shares of state-owned companies listed in the IDXBUMN20 index on the Indonesia Stock Exchange. The population was 20 issuers and using purposive sampling, 13 issuers were obtained as samples. By using a single index model, the results show that 7 stocks make up the optimal portfolio with the proportion of funds as follows ANTM (27.52%), BBNI (24.02%), PTBA (17.86%), BMRI (15.08%), TINS (7.51%), BBRI (7.45%) and PGAS (0.56%). Measurement of portfolio performance using the Treynor method of 0.17233 is higher than market performance which has a value of 0.01441.